Flotsam - Wiesner, David (New York : Clarion Books, 2006)
The story of what happens when a camera becomes a piece of flotsam.
Recipient, Caldecott Medal
Best Illustrated Children's Book Awards, New York Times Book Review
Keywords: Cameras -- Juvenile fiction; Beaches -- Juvenile fiction; Stories without words; Cameras -- Fiction; Beaches -- Fiction; Caldecott Medal